2018
DOI: 10.30955/gnj.002459
|View full text |Cite
|
Sign up to set email alerts
|

Study of number of total mortality, cardiovascular and Respiratory mortality attributed to air pollutants of Tehran in 2005-2014

Abstract: <p>Over the last few decades, the evidence on the adverse effects on the health of air pollution has been raised. Mortality is the most important health effect of ambient air pollution. We studied the relation between mortality and criteria pollutant air in Tehran, one of the highly industrialized, densely populated area and most polluted cities of the reign, during 2005-2014. For this purpose, we applied the approach proposed by the World Health Organization using the AirQ 2.2.3 model. Hourly concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Pollution is also the most important environmental risk factor in emergence and progression of some diseases including lung cancer, asthma, Alzheimer's and Parkinson's diseases, as well as psychological complications, and devastating effects on fetus and many others (Ghorani-Azam et al 2016;Liu et al 2016;Magari et al 2001). Kermani et al (2018) found that the total number of deaths was more than 53,000 people as a result of air pollution during 2005-2014 in Tehran City of which more than 42,000 deaths were related to cardiovascular and respiratory diseases. During this period, air quality index (AQI) rate was increased by 11.8% where PM 2.5 and PM 10 pollutants played the greatest role in weakening air quality in Tehran City and its resulting hazards (Saniei et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pollution is also the most important environmental risk factor in emergence and progression of some diseases including lung cancer, asthma, Alzheimer's and Parkinson's diseases, as well as psychological complications, and devastating effects on fetus and many others (Ghorani-Azam et al 2016;Liu et al 2016;Magari et al 2001). Kermani et al (2018) found that the total number of deaths was more than 53,000 people as a result of air pollution during 2005-2014 in Tehran City of which more than 42,000 deaths were related to cardiovascular and respiratory diseases. During this period, air quality index (AQI) rate was increased by 11.8% where PM 2.5 and PM 10 pollutants played the greatest role in weakening air quality in Tehran City and its resulting hazards (Saniei et al 2016).…”
Section: Introductionmentioning
confidence: 99%